No one but you - Wood, Douglas, 1951-; Lynch, Patrick James (Somerville, Mass. : Candlewick Press, 2011)
Readers are invited to discover nature using their sense of smell, sight, hearing, touch, and taste.
Keywords: Nature -- Easy picture; Senses and sensation -- Easy picture